Downward Shortwave Irradiance at the Thule High Arctic Atmospheric Observatory (THAAO_DSI) - Meloni, Daniela; Di Sarra, Alcide; Di Iorio, Tatiana; Pace, Giandomenico; Muscari, Giovanni; Iaccarino, Antonio; Calì Quaglia, Filippo (Agenzia Nazionale per le nuove tecnologie, l’energia e lo sviluppo economico sostenibile (ENEA), 2022)
Measurements of downward shortwave (SW) and longwave (LW) irradiances started in 2009 with the installation of one pyranometer and one pyrgeometer on the roof of building 1971 (about 5 m agl). Different models of instruments have been operated: Eppley PSP and Kipp&Zonen CMP21 pyranometers for SW irradiance, and Eppley PIR and Kipp&Zonen CGR4 pyrgeometers for LW irradiance. See https://www.thuleatmos-it.it/instruments/radiometers for additional details.
Radiometers are ventilated to prevent ice/dew formation on their domes. Data are recorded with a 30 second time step and are used to calculate hourly means and standard deviations. Corrections are applied to SW measurements in order to remove the thermal offset and to take into account the cosine response of each pyranometer. SW and LW irradiance measurements from Kipp&Zonen models are obtained accounting for the dependance of the radiometers’ sensitivity on temperature. Regular calibrations allow our team to monitor changes of the sensitivity with time. Quality checks are perfomed based on tests recommended for sensors enrolled in the Baseline Surface Radiation Network (BSRN).
THAAO_DSI
Keywords: climate change; Arctic amplification; surface radiative balance; cloud radiative effect